Effects of Obstructive Sleep Apnea on Cardiac Function and Clinical Outcomes in Chinese Patients with ST-Elevation Myocardial Infarction - Baoxin Liu; Rong Guo; Shunping Zhou; Shuanshuan Xie; Ke Wang; Yawei Xu (The Scientific World Journal)
Aim. The objective of this study was to investigate the influence of OSA on cardiac function in Chinese patients with ST-elevation myocardial infarction (STEMI) and determine the prognostic impact of OSA among these patients. Methods. In this retrospective study, 198 STEMI patients were enrolled. Doppler echocardiography was performed to detect the effect of OSA on cardiac function. Major adverse cardiac events (MACE) and cardiac mortality were analyzed to determine whether OSA was a clinical prognostic factor; its prognostic impact was then assessed adjusting for other covariates. Results. The echocardiographic results showed that the myocardium of STEMI patients with OSA appeared to be more hypertrophic and with a poorer cardiac function compared with non-OSA STEMI patients. A Kaplan-Meier survival analysis revealed significantly higher cumulative incidence of MACE and cardiac mortality in the OSA group compared with that in the non-OSA group during a mean follow-up of 24 months. Multivariate Cox regression analysis revealed that OSA was an independent risk factor for MACE and cardiac mortality. Conclusion. These results indicate that the OSA is a powerful predictor of decreased survival and exerts negative prognostic impact on cardiac function in STEMI patients.